Impact of renal transplantation on glucose tolerance in Japanese recipients with impaired glucose tolerance. Issue 4 (7th October 2016) - Nakamura, A.; Iwami, D.; Miyoshi, H.; Morita, K.; Taguri, M.; Terauchi, Y.; Shinohara, N.; Atsumi, T.
Abstract: Aims: To investigate changes in glucose tolerance, insulin secretion and insulin sensitivity in Japanese recipients before and 1 year after renal transplantation. Methods: We conducted a study of Japanese recipients without diabetes who underwent renal transplantation at Hokkaido University Hospital. A 75‐g oral glucose tolerance test was performed before and 1 year after renal transplantation in these recipients. Insulin sensitivity was estimated using the Matsuda index and homeostasis model assessment of insulin resistance (HOMA‐IR). Insulin secretion was evaluated based on the insulin secretion sensitivity index‐2 (ISSI‐2). Results: Of the 62 renal transplant recipients, 31 were diagnosed as having impaired glucose tolerance before transplantation. Among these 31 recipients, after 1 year, four had developed new‐onset diabetes after transplantation, and nine had impaired glucose tolerance. Unexpectedly, 18 changed from impaired to normal glucose tolerance. When these recipients with impaired glucose tolerance were classified into a non‐amelioration group and an amelioration group, the ISSI‐2 was significantly reduced, with no significant changes in the Matsuda index or HOMA‐IR, in the non‐amelioration group 1 year after renal transplantation. By contrast, ISSI‐2 and Matsuda index values were significantly increased, with no significant changes in HOMA‐IR values in the amelioration group. Conclusions: More than half of Japanese renal transplant recipients with impaired glucose tolerance had normal glucose tolerance 1 year after renal transplantation. These results suggest that an increase in insulin secretion and whole insulin sensitivity was associated with improvement in glucose tolerance in these recipients. What's new?: More than half of Japanese renal transplant recipients with impaired glucose tolerance had improved to normal glucose tolerance 1 year after renal transplantation. An increase in insulin secretion and whole insulin sensitivity could be associated with an improvement in glucose tolerance in these recipients.